Evolution of hole surface integrity in successive processing using sequential milling and laser shock peening. (March 2022) - Gu, Huiqing; Jiao, Li; Yan, Pei; Cheng, Minghui; Du, Kai; Song, Yifan; Qiu, Tianyang; Wang, Xibin
Abstract: Part's surfaces are usually produced by successive/integration machining process and the performance of the part is directly tied to the generated surface integrity. Holes are commonly used in many critical engineering structures to connect parts, whose surface primarily characterizes a high risk of fretting or contact fatigue failure. In this paper, the evolution of metallurgical and mechanical surface integrity of Ti-6Al-4V alloy hole surface which machined using multi-step milling and successive laser shock peening (LSP) treatment was investigated. Firstly, a special workpiece with various hole surface pieces was designed and four different sequential milling processes were set to conduct the milling experiments. A comprehensive analysis of the evolution of surface roughness, microstructure, microhardness, and residual stress along the sequential processing steps was carried out. The results showed that the forms of surface integrity evolution could be classified into mono-evolution and coupling evolution, which were correlated to the combined effect of the milling parameters, cutter-workpiece engagement nature, milling sequence, milling mode, and the coolant/lubricant applied strategy. Mono-evolution was predominated in material removal sequences (milling sequences), while the coupling evolution was dependent on the radial depth of cut (DoC, 50 μm). By comparison, coupling evolution was prominent in non-material removal related sequences (LSP treatment). Due to the conformal contact nature of tool-workpiece engagement and the flood cooling strategy, the microhardness in the subsurface layer was not significantly altered in milling sequences, except that the up-milling normally produced a surface with lower hardness and the down-milling produced almost unchanged surface hardness compared with bulk material. The residual stress was a result of the coupling effect of the residual stress field introduced in the previous and current machining sequences, whose in-depth distribution could be represented as an exponential decay function. The degree of influence of the machining sequences and their interactions on the final residual stresses could be evaluated by utilizing a set of weighting coefficients. This research indicated that understanding the effect of successive processing on the surface integrity evolution could help in planning of appropriate processes to achieve desirable surface integrity. Graphical abstract: Unlabelled Image Highlights: Mono-evolution of surface integrity dominates in the material removal sequences. Coupling evolution of surface integrity dominates in non-material removal process. Microhardness is determined by tool-workpiece engagement and cooling strategy. The residual stress profiles could be regarded as exponential decay function. Machining steps and their coupling interaction on residual stress can be evaluated.